Tanggungjawab Pemerintah Daerah Terhadap Konsumen Selama Pandemi Covid-19 - Gunawan; Lasatu, Asri; Patila, Manga’ (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
The government as a public servant has responsibilities that are not limited by space, time, and circumstances. The government has an obligation to provide services to the community anytime and anywhere and under any circumstances, including disaster emergencies. COVID-19 is a disaster that limits the movement of every human being, including the government. However, government services to the community must still run in order to fulfill the basic needs of the community. One form of the government's responsibility during the Pandemic Period is to provide legal protection to every consumer. The problem in this research is how is the implementation of local government responsibilities to consumers during the Covid-19 Pandemic? This study used several approaches, the data were analyzed qualitatively-quantitatively, and the results were in the form of analytic descriptive. The conclusion of the research is that during the Covid-19 pandemic, the local government has carried out its responsibilities in accordance with laws and regulations, but not optimally according to consumer expectations.